Frankies For You (FFY) - Dave, Shruti (SAGE Knowledge. Cases., 2017)
Frankies For You is a comprehensive case on standard costing. It stresses the importance of adopting cost control tools like budgeting by small organizations. FFY is a small food joint started by Mr. Raj Singh. After the first month of operation, he finds that though sales volume has increased compared to the budget, the actual profit has fallen. Detailed variance analysis has to be used to find the cause for this anomaly, to evaluate the performance of the staff and to assign responsibilities. The case also refers to Activity Based Pricing, an important contemporary costing principle.